A computational study of non-coding RNAs on the regulation of activating transcription factor 3 in human breast cancer cells. (December 2020) - Akshaya, R.L.; Akshaya, N.; Selvamurugan, N.
Graphical abstract: Highlights: ATF3 overexpression correlated with breast cancer progression. In silico analysis identified the miRNAs that putatively target ATF3. Expression of mir-3674 (ATF3 target) increased in human breast cancer cells. A sponging effect of miR-3674 by lncRNAs for non-targeting of ATF3 was speculated. A sponging effect of miR-3674 by circRNAs for non-targeting of ATF3 was speculated. Abstract: We previously reported that activating transcription factor 3 (ATF3), an adaptive response gene, plays a dichotomous role in regulating several molecular processes during breast cancer progression. ATF3 promoted the expression of runt-related transcription factor 2 (Runx2, a metastatic gene) and activated matrix metalloproteinase 13 (MMP13, an invasive gene), thereby fostering proliferation and bone-metastasis of the breast cancer cells. Targeting ATF3 may mitigate the metastatic spread of breast cancer and improve the patient's lifespan. Non-coding RNAs (ncRNAs) such as microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs) are the new-era regimens that are currently utilized for diagnosis and treatment of a variety of malignancies including cancer. mir-3674 putatively targets ATF3, but its expression was significantly increased in human breast cancer cells (MDA-MB231), compared to normal human mammary epithelial cells (MCF-10A). Our in silico analysis identified a few lncRNAs and circRNAs showing their putative binding sites for miR-3674. Thus, mir-3674, despite its abundance in the MDA-MB231 cells, could not effectively target ATF3, which could be due to the sponging mechanism of lncRNAs and circRNAs towards mir-3674. More extensive in vitro and in vivo studies are required to validate this and expand the diagnostic and therapeutic perspectives of breast cancer.